FEMALE MORTALITY FROM BREAST CANCER IN THE STATE OF PARÁ BETWEEN 2015 AND 2019 - Castro Júnior, José Wilker Gomes de; Sousa, José Pedro da Silva; Tholius, Beatriz Siems; Miranda, Anna Luiza Alves de Oliveira; Macedo, Érika Maria Carmona Keuffer Cavalleiro de (Mastology, 2021)
Introduction: Breast cancer is the most common type of cancer among women worldwide. This pattern is related to dif- ferent risk factors such as diet, race, heredity, hormonal diseases, tobacco and alcohol use, which contribute to the inci - dence of breast cancer¹. A late diagnosis is one of the biggest obstacles related to the treatment of this pathology since in Brazil there are no adequate conditions for the screening of the disease. Objectives: The objective of the present study is to analyze the epidemiological profile of female mortality from breast cancer in the state of Pará between 2015 and 2019. Methods: This is an exploratory, quantitative study. Only women, of any age, were analyzed using the Technology Department of the unified health system (Departamento de Informática do Sistema Único de Saúde – DATASUS) as a database between 2015 and 2019, in the state of Pará, Brazil. Results: Among the 3,426 women who died of breast cancer between 2015 and 2019 in Pará, 89.66% stated they were brown, 28.45% were between 40 and 49 years of age, and 82.31% of them lived in the city of Belém. Moreover, the years that showed the highest mortality rates were 2019, 2018 and 2017 with 838, 785, and 733 deaths, respectively. Conclusions: The findings of this study showed that some aspects affect more the incidence of breast cancer, among which race-related factors, age over 40 years, and residency in the capital city of Belém are the most relevant. Besides, it is crucial to understand the progressive increase in cases tracked over the last years. These data confirm the necessity of an intervention in the health system operating in the state of Pará.